Factors contributing to job stress in public services: a case of Jabatan Kesihatan Negeri Melaka / Nurul Nadhirah Abdul Aziz - Abdul Aziz, Nurul Nadhirah (Faculty of Business and Management, 2018)
Due to era globalization, the nature of work have change and requires employees more skills, more time, more comfortable physical environment in the workplace to improve their work performance. Thus, in time with increasingly diverse the ability to adapt with changes is the most important components that employees should focus on and the organization needs to look for the important elements that will affect job stress among employees. Therefore, job stress is the harmful physical and emotional responses that occur when the requirements of the job do not match the capabilities, resources, or needs of the employees. Therefore, the purpose of this research is to investigate the factors contributing to job stress in public services in Jabatan Kesihatan Negeri Melaka. This study used simple random sampling techniques and personally administered questionnaires as an instrument to collect data. The data from 70% out of 181 employees are collected then evaluated by using Statistical Package for the Social Science (SPSS) Version 22 Software. The result from Multiple Regression analysis indicates that all the elements in job stress which is role conflict, role ambiguity, work overload and work family conflict have positive significant relationship. Moreover, it has revealed that, role conflict found to be most influential variables towards job stress among employees at Jabatan Kesihatan Negeri Melaka.